Structural breaks, cointegration and demand for money in Nigeria - Sani I. Doguwa; Olorunsola E. Olowofeso; Stephen O. U. Uyaebo; Ibrahim Adamu; Abiodun S. Bada (CBN Journal of Applied Statistics, 2014)
This paper estimates the money demand function in Nigeria in the aftermath of the recent global financial crisis and examines whether its underlying properties has changed over the years. Specifically, the existence of a stable long-run demand for money function during the period 1991:Q1-2013:Q4, while accounting for the possibility of structural breaks is investigated. The Gregory-Hansen residual based test for cointegration detected both intercept and regime shifts in 2007:Q1 as the null of no cointegration is rejected at 1 per cent significance level, indicating that long run relationship exists between real money supply, real income, real monetary policy rate, exchange rate spread and movements in exchange rate in Nigeria. This estimation technique is robust to structural break, which ensures that the estimated parameters are unbiased. The CUSUMSQ test provides evidence of a stable money demand function before and after the crisis. The paper infers that since the relationship among the variables holds over a fairly long period of time, the estimated money demand model provides important foundations for monetary policy setting in Nigeria.
Keywords: C33; E41; 330; Demand for money; Structural breaks; Cointegration